Preparation of Fouling-Resistant Nanofibrous Composite Membranes for Separation of Oily Wastewater - Yalcinkaya, Fatma; Siekierka, Anna; Bryjak, Marek (Polymers, 2017)
A facile and low-cost method has been developed for separation of oily wastewater. Polyvinylidene fluoride/polyacrylonitrile (PVDF/PAN) nanofibers laminated on a supporting layer were tested. In order to create highly permeable and fouling-resistant membranes, surface modifications of both fibers were conducted. The results of oily wastewater separation showed that, after low vacuum microwave plasma treatment with Argon (Ar) and chemical modification with sodium hydroxide (NaOH), the membranes had excellent hydrophilicity, due to the formation of active carboxylic groups. However, the membrane performance failed during the cleaning procedures. Titanium dioxide (TiO₂) was grafted onto the surface of membranes to give them highly permeable and fouling-resistance properties. The results of the self-cleaning experiment indicated that grafting of TiO₂ on the surface of the membranes after their pre-treatment with Ar plasma and NaOH increased the permeability and the anti-fouling properties. A new surface modification method using a combination of plasma and chemical treatment was introduced.
Keywords: nanofiber; modified nanofiber; nanocomposite